(untitled) (Bangladesh Journal of Botany, 2015)
Genetic and epigenetic changes (DNA methylation) in the mother plants of somatic hybrids (1st cycle) and their regenerants (30th cycles sub-cultured) were analyzed using methylation-sensitive ISSR and RAPD markers. ISSR and RAPD profiles and their cluster analyses based on the Jaccards similarity coefficient revealed 100% genetic similarity among the mother plant and their regenerants. While for the epigenetic changes in the samples, the MS-ISSR markers detected DNA methylation (2.7%) in the regenerants compared to the mother plant (1%), whereas MS-RAPD markers detected a little methylation patterns in the regeneratns (0.6%) compared to the mother plants (0.4%). DOI: http://dx.doi.org/10.3329/bjb.v44i1.22722 Bangladesh J. Bot. 44(1): 45-50, 2015 (March)